食用植物油煎炸过程中的品质变化Quality changes of edible vegetable oils during frying - 厉玉婷1，2，于艳艳1，2，杨振东1，2，程月红1，2，师景双1，2，鲍连艳1，2，任雪梅1，2 LI Yuting1,2, YU Yanyan1,2, YANG Zhendong1,2, CHENG Yuehong1,2, SHI Jingshuang1,2, BAO Lianyan1,2, REN Xuemei1,2 (Zhongguo youzhi, 2023)
利用花生油、大豆油、调和油、棕榈油4种食用植物油作为煎炸油对豆腐、裹粉鸡柳、油条3种食材进行煎炸，研究煎炸时间对煎炸油极性组分含量及羰基值的影响，确定煎炸油时间预警点，同时研究了不同煎炸油品种、不同食材对煎炸油极性组分含量的影响。结果表明：极性组分含量、羰基值均与煎炸时间呈正相关（r极性组分=0809，r羰基值=0.859，P=0.000）； 煎炸6~11 h煎炸油极性组分含量均值从初始的11.85%增至20.96%，最大值为34.10%，可作为煎炸油质量不达标的时间预警点；煎炸12 h，极性组分含量从低到高依次为花生油、棕榈油、调和油、大豆油，含量分别为211%、24.1%、26.8%、27.8%，豆腐、裹粉鸡柳、油条煎炸油中极性组分含量分别为17.7%、250%、322%；煎炸18 h，极性组分含量增大程度由低到高为棕榈油/调和油、大豆油、花生油，煎炸食材用油为豆腐煎炸油、裹粉鸡柳煎炸油、油条煎炸油。 Four kinds of edible vegetable oil including peanut oil, soybean oil, blended oil and palm oil were used to fry three kinds of food stuffs including tofu, chicken fillet wrapped in flour and fried dough sticks. The effects of frying time on the polar compounds content and carbonyl value of frying oil to fix the early warning time of frying oil, and the effects of different frying oil and food stuffs on the polar compounds content of frying oil were studied. The results showed that polar compounds content and carbonyl value were positively correlated with frying time (rpolar compounds=0.809, rcarbonyl value=0.859,P=0.000). The mean value of polar compounds content increased from 11.85% to 20.96% after frying for 6-11 h, and the maximum value was 34.10%, which could be used as the early warning time for the quality of frying oil. The polar compounds content in the frying oil after frying for 12 h from low to high were as follows:21.1% for peanut oil, 24.1% for palm oil, 26.8% for blended oil, 27.8% for soybean oil, and 17.7% for tofu frying oil, 25.0% for chicken fillet wrapped in flour frying oil, 32.2% for fried dough sticks frying oil. After frying for 18 h, the increase of polar compounds content in different frying oil and different fried food oils from low to high were as follows: palm oil/blended oil, soybean oil, peanut oil, and tofu frying oil, chicken fillet wrapped in flour frying oil, fried dough sticks frying oil.